Effect of Corrosion Time on the Corrosion Behavior of N80 Steel in 0.5 MPa CO2 Simulated Oilfield Water - SHI Yun-sheng, YANG Hong, GAN Lei, DENG Kuan-hai, FAN Chun-ling, LIN Yuan-hua (Cailiao Baohu)
At present, the effect of corrosion time on the corrosion behavior of N80 oil casing steel in 0.5MPa CO2 environment has less been studied.By the means of SEM, XRD, EDS and electrochemical test, the effect of corrosion time on the corrosion behavior of N80 steel in simulated oilfield water with 0.5 MPa CO2 at 70 ℃.Results showed that the corrosion time affected the corrosion behavior through influencing the composition, thickness and compactness of the corrosion product film.In the first 24 h of corrosion, only irregular and isolated FeCO3 grains were produced on the surface of samples, and the product film was not completely covered on the substrate.After 48 h of corrosion, FeCO3 grains grew and connected with each other to form an uniform and dense corrosion film.After 96 h of corrosion, CaCO3 grains began to precipitate on the product film, and FeCO3 grains continued to grow.At 192 h of corrosion, a large number of CaCO3 grains covered the surface of FeCO3 grains, which formed a dense product composite film.With the increase of corrosion time, the corrosion film continued to be thicker and denser, and the corrosion rate continued to decrease.